Removal of chromium(III) from aqueous waste solution by liquid-liquid extraction in a circular microchannel - Luo, Jian Hong (Water science and technology : a journal of the International Association on Water Pollution Research, 2017)
A new circular microchannel device has been proposed for the removal of chromium(III) from aqueous waste solution by using kerosene as a diluent and (2-ethylhexyl) 2-ethylhexyl phosphonate as an extractant. The proposed device has several advantages such as a flexible and easily adaptable design, easy maintenance, and cheap setup without the requirement of microfabrication. To study the extraction efficiency and advantages of the circular microchannel device in the removal of chromium(III), the effects of various operating conditions such as the inner diameter of the channel, the total flow velocity, the phase ratio, the initial pH of aqueous waste solution, the reaction temperature and the initial concentration of extractant on the extraction efficiency are investigated and the optimal process conditions are obtained. The results show that chromium(III) in aqueous waste solution can be effectively removed with (2-ethylhexyl) 2-ethylhexyl phosphonate in the circular microchannel. Under optimized conditions, an extraction efficiency of chromium(III) of more than 99% can be attained and the aqueous waste solution can be discharged directly, which can meet the Chinese national emission standards